Seeking stability in Chicago: School actions, (c)overt forms of racial injustice, and the slow violence of neoliberal rationality - Ann M. Aviles; Jessica A. Heybach (Education Policy Analysis Archives, 2017)
During the 2012-13 school year, Chicago Public Schools (CPS) reported 18,669 students were enrolled in the Students in Temporary Living Situations (STLS) program. In this paper, we seek to discuss school closings in relationship to their impact on poor, unstably housed, black students in Chicago. Critical race theory (CRT) constructs of (1) whiteness as property (Harris, 1995), (2) racial realism (Bell, 1992; Buras, 2013), and (3) white supremacy as education policy (Donnor, 2013; Gillborn, 2005) will be the frames in which we situate and analyze the school actions that have resulted in the recent closure/consolidation of 49 Chicago Public Schools (CPS). We contend that these constructs related to race, when mixed with neoliberal rationality (Brown, 2015) conspire to foster disastrous school policy that unduly impacts vulnerable populations and de-democratizes Chicago in profound ways. For this project, the CPS STLS program manager overseeing STLS transitions during the 2012-13/2013-14 school actions, and civil rights lawyers-advocates who have spent over two decades working to enforce McKinney-Vento implementation in CPS were interviewed. Document analysis of court records regarding three cases through which the Chicago Public Schools were named as Defendants in litigation brought forth by families (parents and students) impacted by CPS’ school actions; Chicago Teacher’s Union data and IL General Assembly’s Chicago Educational Facilities Task Force were completed. Findings reveal in order to promote equitable, and effective education policy for students of color experiencing housing instability means working against white supremacy and slow violence found throughout the US and world.